Hubungan Daya Ledak Otot Tungkai dengan Keterampilan Tendangan Lurus Atlet Pencak Silat - Kiki Gustama; Rais Firlando; Wawan Syafutra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2021)
This study aimed to determine the relationship between the explosive power of the leg muscles and the straight kick skills of the new Cimande Taba Pencak Silat college athletes in Lubuklinggau City. This research is a correlational study. The population in this study was the male pencak silat athlete Cimande Taba Baru, Lubuklinggau City. The samples taken from the total sampling were 20 male pencak silat athletes. The research method used is a quantitative approach with correlational methods, with data collection techniques using tests and measurements. The instrument for measuring leg muscle explosive power is using a standing brood jump test and for straight kick skills using a straight kick speed test. The data analysis technique uses Pearson product moment correlation and normality prerequisite test. The results showed that: There was a significant relationship between the explosive power of the leg muscles and the straight kick skills of the new Cimande Taba Pencak Silat college athletes, Lubuklinggau City, with the value of rcount = 0.555. > r table = 0.444. Coefficient of Determination (KD) = 30.8%. In conclusion, the alternative hypothesis is accepted. Keywords: Explosive Power of Leg Muscles, Straight Kick Skills